2019
DOI: 10.1186/s12909-019-1663-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of medical student retention of clinical skills following simulation training

Abstract: Background Adequate clinical skills training is a challenge for present day medical education. Simulation Based Education (SBE) is playing an increasingly important role in healthcare education worldwide to teach invasive procedures. The impact of this teaching on students along with retention of what is taught is not fully understood. The purpose of this study was to evaluate the retention levels of practical skills taught and assessed by SBE and to explore the degree of re-training required to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 15 publications
6
55
0
2
Order By: Relevance
“…To overcome this problem, we believe that simulation-based education (SBE) can be a powerful solution to compensate for the lack of opportunities to exercise these skills [22]. As SBE methods have been developed and are widely used to acquire both technical and non-technical skills in medical education [23] [24], combination of SBE and CC could potentially maximize the competency of medical students. For example, medical students can rephrase the resuscitation utilizing simulator which they watched in the emergency ward.…”
Section: Plos Onementioning
confidence: 99%
“…To overcome this problem, we believe that simulation-based education (SBE) can be a powerful solution to compensate for the lack of opportunities to exercise these skills [22]. As SBE methods have been developed and are widely used to acquire both technical and non-technical skills in medical education [23] [24], combination of SBE and CC could potentially maximize the competency of medical students. For example, medical students can rephrase the resuscitation utilizing simulator which they watched in the emergency ward.…”
Section: Plos Onementioning
confidence: 99%
“…Among the numerous evolving teaching methods in recent decades, simulation has been proved one of the most effective methods with the advantage of guarantying standardized learning experience (Weller et al, 2012). A recent study demonstrated that simulation-based education with deliberate practice significantly improved the confidence and clinical competence of students (Offiah et al, 2019). In addition to alleviating the fear of neurology, simulation-based education could also inspire the academic interest of students (Galtrey et al, 2018).…”
Section: The Preference Of Participants With the Three Bedside Teaching Methodsmentioning
confidence: 99%
“…Students can practice and reinforce newly learned skills to the level of mastery through simulation-based training combined with a feedback mechanism [8,9]. Compared to clinical training with real patients, simulation training is safer and allows for the acquisition of clinical skills through deliberate repeated practices [10,11]. During the pandemic period, students lacked access to PPE, which was in high demand.…”
Section: Introductionmentioning
confidence: 99%